Negative Correlation Between Social Support and Exam Anxiety Among Indonesian High School Students - Sylvia Lim; Sabrini Mentari Rezeki; Catherine Olisa; Marcell Engrasia; Fannesya Halim; Rina Mirza (Da'wa Faculty of Islamic State University Salatiga, 2026)
Changes in educational policies in Indonesia in recent years have often created uncertainty for students. During adolescence, high academic demands, particularly when facing examinations, frequently trigger stress and anxiety. In this context, social support from parents, peers, and teachers plays an important role in helping students manage the pressures they experience. This study aims to examine the relationship between social support and anxiety among students of SMA Global Prima Medan. The research employed a quantitative approach with a correlational design. The subjects consisted of 142 students selected through proportionate stratified random sampling. The instruments used were the social support scale and the anxiety scale. Data were analyzed using Pearson’s Product-Moment Correlation. The results indicated a significant negative relationship between social support and anxiety, with r = –0.179 and p = 0.033 (p < 0.05). This means that the higher the social support received by students, the lower their anxiety levels. The coefficient of determination (R²) is 0.035, indicating that social support contributes 3.2% to anxiety, while the remaining 96.8% is influenced by other factors outside this study. In conclusion, social support plays a role in reducing student anxiety, although its contribution is relatively small. These findings emphasize the importance of parents, peers, and teachers in creating a supportive environment for students.